THE IMPORTANCE OF INFORMATION TECHNOLOGY IN MEDICINE - Mirzo Ulugbek Rahimov; Fazliddin Arzikulov (Web of Journals Publishing, 2026)
This article highlights the role and importance of information technologies in the modern healthcare system. It is shown that the quality, speed and accuracy of medical services are increasing through technologies such as medical information systems, electronic documents, telemedicine, and remote monitoring. At the same time, the issues of medical data security and compliance with ethical standards are also analyzed. At the end of the article, conclusions are drawn on the prospects of information technologies in medicine.
Keywords: Medicine, information technology, electronic medical records, telemedicine, remote monitoring, information security, healthcare.